The impact of dietary habits and practices during adolescence on the risk of obesity: the birth to twenty cohort - Feeley, Alison Bridget Bernadette (My University, 2013)
Background: South Africa is not exempt from the obesity epidemic and latest figures show that a third of adult men and two-thirds of adult women are either overweight or obese. Concomitant are changes in dietary habits and practices which have been implicated in the risk of obesity. Concern is that obesity and related non-communicable diseases (NCDs) manifest at younger ages. Adolescence, as well as being a stage during the life course when eating attitudes and behaviours are formed, is a particular time when the aetiology of NCDs becomes evident. Little is known about the dietary patterns during adolescence in South Africa, and if policymakers are to attempt to reduce the burgeoning statistics relating to obesity then it is important to understand adolescent dietary habits and eating practices. Aims: To describe adolescent dietary habits and practices among South African adolescents and how they might influence obesity risk. Methods: This study used a mixed methods study design, using both historical and prospective data and included four study components in both an urban (components 1-3) and a rural setting (component 4). Firstly, a cross-sectional assessment of fast-food intake of urban 17-year-olds from the Birth to Twenty Cohort (Bt20); secondly, a longitudinal descriptive analysis of dietary habits and practices of the Bt20 participants over a five-year period, between ages 13 – 17 years followed; thirdly a longitudinal assessment of the relationship between dietary habits, change in socio-economic status (SES) and obesity in the Bt20 adolescents was conducted; and finally, an exploratory survey assessing the availability of fast foods in a rural area. Results: The cross-sectional analysis showed that mean fast food intake was 8.1 (4.6) items and 7.2 (4.7) items/week for males and females respectively. Furthermore, the kota (or quarter) was the most popular fast food item and on average it provided 5 370 kJ, 51 g fat (of which 13 g Saturate fatty acids (SFA)). The longitudinal analysis showed that poor dietary habits and practices were embedded by the age of 13 years and were characterised by: high fast food consumption with at least five items/week consumed from the age of 13 years. Breakfast (weekday and weekend) consumption declined for both genders and females ate breakfast less regularly than males. Snacking while watching television increased with age: with females consuming more (4.0 (4.8) - 7.3 (5.9)) snacks per week than males (3.3 (4.5) - 6.0 (5.8). Two-thirds of participants ate their main meal with their family but among girls there was a trend towards eating this meal less regularly with increasing age. Confectionery consumption remained the same, around nine items/week for males and 10 items/week for females. Lunch box usage declined with age, conversely the number of tuck shop purchases increased with age. The prevalence of combined overweight and obesity was (8.1%) and (27%) in 17-year-old males and females respectively. In males only, soft drink consumption was associated with obesity denoted by BMI z-score and fat mass (p<0.05). In the final multivariate model, soft drink consumption remained positively and significantly associated with both outcomes and „acquiring‟ a fridge over the 12-year period remained negatively associated with both BMI z-score and fat mass (p<0.001). Among females, no associations were found. Thus further data on other lifestyle variables are needed to understand better the exposures related to obesity risk in females. In the rural setting fast food was found to be available albeit a limited variety; two-thirds of the collected samples were either vetkoek (fried dough balls) or fried chips (yielding between 943 kJ – 5 552 kJ and 11 g – 64 g fat). Compared to the kotas available in Soweto, the samples obtained in the rural setting contained more energy and fat (6 300 kJ, 60 g fat vs. 5 369 kJ, 51.5 g fat). Conclusions: This research highlights that poor dietary habits and practices prevail in adolescence which may be implicated in negative health outcomes in later life. Of concern is the finding that poor dietary habits were embedded by the age of 13 years which suggests that interventions need to target families and children prior to adolescence in order to reduce the pervasiveness of these habits in the older child. The prevalence of combined overweight and obesity is higher than the national statistics for both boys and girls at the age of 17-years. This research confirms that some dietary behaviours are associated with obesity risk namely soft drink consumption – but in males only. However soft drink consumption may be a marker for other lifestyle behaviours associated with obesity. Other dietary habits were not shown to be associated with obesity in neither males nor females, which highlights the difficulty in the measurement of exposures relating to diet. This study also showed in males at least, that socio-economic factors are important when considering obesity risk. The availability of fast foods in a relatively impoverished rural area is concerning as it may indicate that this community is undergoing nutritional changes such as those seen in urban environments. With urbanisation and economic transition, households experience a change in SES and these changes drive behaviour which can either enable or disable health outcomes. In this study SES improvement, e.g. fridge ownership seems to enable certain behaviours which can be obesogenic. However we cannot halt development in this context but we must devise ways to improve lifestyle choices which will promote health rather than impede it.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Health Sciences, 2012
Keywords: dietary habits; eating practices; adolescents; urban; rural; fast food; obesity; South Africa